Determinants of Post-Odontectomy Complications: A PLS-SEM Analysis of Clinical Pathway Effectiveness and Patient Risk Profiles - Rachman Indharmawan; kusbaryanto kusbaryanto (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2026)
This study analyses the effect of clinical pathway implementation on post-odontectomy complications. It examines the influence of patient-related factors on postoperative outcomes at the Dental and Oral Hospital of Universitas Airlangga. Globally, oral diseases remain a major public health burden, emphasizing the need to improve the quality and safety of dental surgical care. However, evidence on the effectiveness of clinical pathways in minor oral surgery, particularly in developing countries, remains limited. A quantitative cross-sectional approach was applied using a survey method. A total of 107 participants were included in this study, consisting of 97 odontectomy patients and 10 healthcare professionals selected through purposive sampling. Data were collected from clinical pathway documents, medical records, and structured questionnaires and analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM). The results show that patient-related factors have a significant positive effect on post-odontectomy complications (β = 0.855; p < 0.001), indicating that age, comorbidities, and adherence to postoperative instructions are key determinants. In contrast, Clinical Pathway implementation has no significant direct effect (β = −0.012; p = 0.406) and does not moderate the relationship between patient factors and complications (β = −0.028; p = 0.296). The model demonstrates strong explanatory power (R² = 0.731). These findings suggest that improving postoperative outcomes requires strengthening patient-centered risk assessment and more effective, consistent implementation of clinical pathways in practice Keywords: Clinical Pathway, Odontectomy, Postoperative Complications, Patient Factors, Healthcare Quality